Osteomyelitis in infantile osteopetrosis: A case report with review of literature - Roopashri R; Gopakumar R; Subhas B (Wolters Kluwer Medknow Publications, 2008)
Osteopetrosis is a rare genetic disorder that causes generalized sclerosis of bone due to a defect in bone resorption and remodeling. Dental abnormality may be attributed to pathological changes in bone remodeling. Osteomyelitis is well documented as a complication of osteopetrosis. This disease can be severe and difficult to treat in the osteopetrotic patient. This is a case of 10-year-old girl previously diagnosed as suffering from osteopetrosis and presenting with the complaint of swelling of jaw with extra-oral draining sinus.